Hubungan Antara Kecerdasan Moral Terhadap Perilaku Cybersex Pada Remaja - Nandini Luthfiya; Maya Yasmin (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research aims to examine the relationship between moral intelligence and cybersex behavior among adolescents. The methodology employed in this study involves the use of the product-moment correlation test, encompassing 270 adolescents aged 15 to 19 as research subjects. The Moral Competence Inventory (MCI) developed by Lennick and Kiel (2005) was utilized as the measure of moral intelligence, while the instrument for cybersex behavior originated from tools compiled by Delmonico and Miller (2003). The correlation result of -0.317, p = 0.000 (p < 0.05), indicates a negative relationship between moral intelligence and cybersex behavior among adolescents. It signifies that higher moral intelligence correlates with lower cybersex engagement among adolescents, and conversely, lower moral intelligence associates with increased cybersex activity among this demographic. One approach to address cybersex behavior is by enhancing adolescents' understanding of moral values.